Evaluation of cebranopadol, a dually acting nociceptin/orphanin FQ and opioid receptor agonist in mouse models of acute, tonic, and chemotherapy-induced neuropathic pain - Sałat, Kinga (Inflammopharmacology, 2017)
BACKGROUND: Cebranopadol (a.k.a. GRT-6005) is a dually acting nociceptin/orphanin FQ and opioid receptor agonist that has been recently developed in Phase 2 clinical trials for painful diabetic neuropathy or cancer pain. It also showed analgesic properties in various rat models of pain and had a better safety profile as compared to equi-analgesic doses of morphine. Since antinociceptive properties of cebranopadol have been studied mainly in rat models, in the present study, we assessed analgesic activity of subcutaneous cebranopadol (10 mg/kg) in various mouse pain models. METHODS: We used models of acute, tonic, and chronic pain induced by thermal and chemical stimuli, with a particular emphasis on pharmacoresistant chronic neuropathic pain evoked by oxaliplatin in which cebranopadol was used alone or in combination with simvastatin. KEY RESULTS: As shown in the hot plate test, the analgesic activity of cebranopadol developed more slowly as compared to morphine (90–120 min vs. 60 min). Cebranopadol displayed a significant antinociceptive activity in acute pain models, i.e., the hot plate, writhing, and capsaicin tests. It attenuated nocifensive responses in both phases of the formalin test and reduced cold allodynia in oxaliplatin-induced neuropathic pain model. Its efficacy was similar to that of morphine. Used in combination and administered simultaneously, 4 or 6 h after simvastatin, cebranopadol did not potentiate antiallodynic activity of this cholesterol-lowering drug. Cebranopadol did not induce any motor deficits in the rotarod test. CONCLUSION: Cebranopadol may have significant potential for the treatment of various pain types, including inflammatory and chemotherapy-induced neuropathic pain.